Implementasi Kebijakan Peningkatkan Kesejahteraan Petani Tembakau di Desa Beroangin, Kecamatan Bangkala Barat, Kabupaten Jeneponto - Supriyanto; Devi, Nourma Ulfa Kumala; Fauzan, Ahmat (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The welfare of tobacco farmers in Probolinggo Regency remains a major issue due to fluctuating market prices, limited access to subsidized fertilizers, and lack of technical training. To address this, the local government issued Regional Regulation No. 30 of 2022, utilizing Tobacco Excise Revenue Sharing Funds (DBHCHT) to support farmer welfare. This study aims to analyze the implementation of the policy in Tamansari Village using George C. Edward III’s policy implementation theory, which emphasizes four key factors: communication, resources, disposition, and bureaucratic structure. A qualitative descriptive method was employed, involving in-depth interviews, field observations, and documentation. The results show that the policy has been implemented in accordance with procedures and has contributed positively to improving the quality of tobacco yields through training and fertilizer assistance. However, several challenges remain, including incomplete beneficiary data, lack of information access, and uneven distribution of agricultural inputs.